Preparation method of high-safety composite gel electrolyte, sodium-ion battery and preparation method of sodium-ion battery
The electrolyte is added to the sodium ion battery to carry out thermal cross-linking polymerization reaction, and the electrolyte is solidified into a gel state, and black phosphorus/graphite coated with polyvinylidene fluoride-hexafluoropropylene is added. Ethylene materials solve the problems of easy leakage and flammability of electrolytes, and improve the safety and performance of the battery.
Patent Information
- Application Number
- CN202411418675.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-31
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-07
AI Technical Summary
The electrolyte of existing sodium ion batteries is prone to leakage and flammable, poses safety hazards, and has low energy density, which limits its application range.
By adding polymer monomers, crosslinking agents and initiators to the electrolyte, an in-situ thermal crosslinking polymerization reaction is generated, forming a network structure to solidify the liquid electrolyte into a gel state, lose its fluidity, and in the electrolyte. Polyvinylidene fluoride-hexafluoropropylene coated black phosphorus/graphene material was added to improve ion transfer speed and cell cycling stability.
It solves the problems of easy leakage and flammability of electrolyte, improves the safety and performance of electrolyte, extends the cycle life of the battery, and improves the safety performance of the battery.
Smart Images

Figure CN119400943A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of batteries, and in particular to a method for preparing a highly safe composite gel electrolyte and a sodium ion battery and a method for preparing the same. Background technology:
[0002] Due to the similar electrochemical properties of sodium ions and lithium ions, both sodium ion batteries and lithium ion batteries received a lot of attention and research in the early stage of battery research. However, studies have found that sodium ion batteries have lower energy density than lithium ion batteries and lack application value in some practical applications requiring high energy density. Therefore, lithium ion batteries are currently widely used in mobile phones, new energy vehicles and other fields. However, the relative scarcity of mineral resources has limited the application scale of lithium ion batteries. In contrast, sodium mineral resources are very abundant. Therefore, it is particularly necessary to solve the problems related to the low energy density of sodium ion batteries and further expand the application of sodium ion batteries.
[0003] Sodium-ion batteries are considered to be an ideal choice for the next generation of energy storage and power batteries due to their abundant raw material reserves and low cost. At present, the electrolyte of sodium-ion batteries still introduces the liquid electrolyte commonly used in lithium-ion batteries. The typical electrolyte is composed of sodium salt, flammable organic carbonate or ether solvent and some functional additives. These common organic solvents are easy to leak, the packaging is not flexible, and they are easy to burn, which poses a great safety hazard. In view of the above problems, a high-safety gel electrolyte for sodium-ion batteries is urgently needed. Summary of the invention:
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a highly safe composite gel electrolyte and a sodium ion battery and a preparation method thereof in view of the deficiencies in the prior art. The present invention adds a polymer monomer, a cross-linking agent and an initiator to the electrolyte to generate an in-situ thermal cross-linking polymerization reaction to form a network structure to firmly wrap the liquid electrolyte, solidify the liquid electrolyte of the sodium ion battery into a gel state, and make the electrolyte lose fluidity, thereby solving the problem that the electrolyte of the existing sodium ion battery is easy to leak and burn. The obtained electrolyte has high safety and good performance, and meets the use requirements of the sodium ion battery.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a highly safe composite gel electrolyte comprises the following steps:
[0007] dissolving electrolyte sodium salt in an organic solvent to prepare a mixed solution;
[0008] Adding polymer monomers, a cross-linking agent and an initiator to the mixed solution to prepare an electrolyte;
[0009] Dissolving polyvinylidene fluoride co-hexafluoropropylene in dimethylformamide, adding black phosphorus nanosheets and graphene nanosheets, performing an ultrasonic treatment, and then removing the solvent to obtain a polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material;
[0010] The polyvinylidene fluoride-co-hexafluoropropylene-coated black phosphorus / graphene material is added to the electrolyte, and a secondary ultrasonic treatment is performed to obtain a composite gel electrolyte.
[0011] Preferably, the organic solvent is one or a mixture of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, propyl acetate and butyl acetate.
[0012] Preferably, the electrolyte sodium salt is at least one of sodium hexafluorophosphate, sodium perchlorate and sodium tetrafluoroborate.
[0013] Preferably, the concentration of the electrolyte sodium salt in the mixed solution is 0.8-2.0 mol / L.
[0014] Preferably, the electrolyte sodium salt is dissolved in the organic solvent by stirring, the stirring time is 4-5 hours, and the temperature during stirring is 20-30°C.
[0015] Preferably, a method for preparing a highly safe composite gel electrolyte further comprises the following steps:
[0016] After the electrolyte sodium salt is dissolved, tris(trimethylsilyl)phosphite and ethyl trifluoroacetate are added to the organic solvent.
[0017] Preferably, the amount of tris(trimethylsilyl)phosphite added is 1-2% by volume of the organic solvent, and the amount of ethyl trifluoroacetate added is 5-10% by volume of the organic solvent.
[0018] Preferably, the polymer monomer is one or more of methyl methacrylate, ethylene oxide, tetrafluoroethylene, and acrylonitrile.
[0019] Preferably, the crosslinking agent is one or more of toluene diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and tris(pentafluorophenyl)borane.
[0020] Preferably, the initiator is an azo compound, and the azo compound is one or more of azobisisobutyronitrile, azobisisoheptanenitrile and methyl azobisisobutyrate.
[0021] Preferably, the polymer monomer, cross-linking agent and initiator are added to the mixed solution and then stirred.
[0022] Preferably, the weight proportion of the polymer monomer in the gel electrolyte is 10-30%, the weight proportion of the cross-linking agent is 5-15%, and the weight proportion of the initiator is 1-5%.
[0023] Preferably, the mass ratio of the polyvinylidene fluoride co-hexafluoropropylene, black phosphorus nanosheets and graphene nanosheets is 1:(0.001-0.002):(0.001-0.002); the addition amount of the polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material when mixed with the electrolyte is 2-5% of the mass of the electrolyte.
[0024] Preferably, the power of the first ultrasonic treatment is 300-500 W, and the time is 0.5-1 hour; the power of the second ultrasonic treatment is 300-500 W, and the time is 1-2 hours.
[0025] In order to better solve the above technical problems, the present invention also provides the following technical solutions:
[0026] A method for preparing a sodium ion battery comprises injecting the composite gel electrolyte prepared by the present invention into a battery, placing the battery under a temperature condition of 50-80° C. for a thermal polymerization cross-linking reaction for 3-8 hours after packaging, so that the composite gel electrolyte forms a gel, thereby preparing a sodium ion battery.
[0027] Preferably, a sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the gel is provided between the positive electrode sheet and the separator, and between the negative electrode sheet and the separator; further, the positive electrode sheet comprises a positive electrode collector and a sodium ion positive electrode active material coated on the positive electrode collector, and the positive electrode active material is at least one of sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium iron phosphate and sodium iron sulfate.
[0028] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:
[0029] The present invention generates an in-situ thermal cross-linking polymerization reaction by adding polymer monomers, cross-linking agents and initiators, thereby forming a network structure to firmly wrap the liquid electrolyte, solidify the electrolyte of the sodium ion battery into a gel state, and make the electrolyte lose fluidity, thereby solving the problems of easy leakage and easy combustion of the electrolyte of the existing sodium ion battery, improving the safety of the electrolyte, and improving the performance of the sodium ion battery; and the gel electrolyte can prevent solid particles such as black phosphorus nanosheets and graphene from piercing the battery separator.
[0030] The present invention also adds an appropriate amount of tris(trimethylsilyl)phosphite and ethyl trifluoroacetate in the electrolyte. Tris(trimethylsilyl)phosphite can improve the photoelectron conduction performance of the electrolyte, enhance the adsorption capacity of the electrolyte to sodium ions, which helps to improve the ion migration rate and the specific conductivity of the electrolyte. In addition, tris(trimethylsilyl)phosphite can also form a dense SEI film, inhibit metal ion dissolution, and improve the cycle stability of the battery. Ethyl trifluoroacetate helps to increase the solubility and electrical conductivity of the electrolyte. At the same time, ethyl trifluoroacetate can also provide a stable environment to prevent the degradation of the electrolyte and the degradation of the electrode.
[0031] The present invention also adds a certain amount of black phosphorus / graphene two-dimensional material coated with polyvinylidene fluoride co-hexafluoropropylene to the composite gel electrolyte. The black phosphorus nanosheet has a serrated edge structure, which has a high selectivity for ion transmission, can effectively capture anions, and significantly increase the number of metal ions transmitted; and the graphene nanosheet has high conductivity and high surface area characteristics, which can increase the transmission speed of sodium ions in the electrolyte and promote the charging and discharging efficiency of the battery. The addition of graphene nanosheets can also effectively make up for the problem that black phosphorus is easy to pulverize in the atmosphere, and the cycle efficiency and cycle stability are poor. Polyvinylidene fluoride co-hexafluoropropylene (PVDF-HFP) has a lower crystallinity, good heat resistance and corrosion resistance, and can resist electrochemical reactions during battery cycling and corrosive substances in the electrolyte, thereby improving the cycle life of the battery. Black phosphorus nanosheets are easy to pulverize when used, so the black phosphorus nanosheets can be prevented from being crushed by polyvinylidene fluoride co-hexafluoropropylene coating, and the cycle stability of the battery using the composite gel electrolyte of the present application is improved.
[0032] In addition, in the gel electrolyte system of the present invention, the gel electrolyte can better coat the surface of the positive electrode material to form a stable protective layer, and the fluidity of the gel electrolyte is relatively low, which can reduce the contact between the electrolyte and the surface of the positive electrode material. Therefore, the gas production of the battery can be better suppressed, which is beneficial to improving the cycle stability of the sodium ion battery, reducing the expansion rate of the battery cell when producing gas, and thus improving the safety performance of the battery. Description of the drawings:
[0033] Figure 1 The appearance diagram of the electrolyte prepared in Examples 1-2 and Comparative Example 1;
[0034] Among them, (a) is the electrolyte of Comparative Example 1; (b) is the composite gel electrolyte prepared in Example 1; and (c) is the composite gel electrolyte prepared in Example 2. Specific implementation method:
[0035] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0036] The following describes a method for preparing a highly safe composite gel electrolyte provided by the present application, comprising the following steps:
[0037] The electrolyte sodium salt is dissolved in an organic solvent to obtain a mixed solution; a polymer monomer, a cross-linking agent and an initiator are added to the mixed solution to obtain an electrolyte; polyvinylidene fluoride co-hexafluoropropylene is dissolved in dimethylformamide, black phosphorus nanosheets and graphene nanosheets are added to the dimethylformamide, an ultrasonic treatment is performed, and then the solvent is removed to obtain a polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material; the polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material is added to the electrolyte, and a secondary ultrasonic treatment is performed to obtain a composite gel electrolyte.
[0038] Based on the above technical scheme, the present invention generates an in-situ thermal cross-linking polymerization reaction by adding a polymer monomer, a cross-linking agent and an initiator, forms a mesh structure to firmly wrap the liquid electrolyte, solidifies the electrolyte of the sodium ion battery into a gel state, and makes the electrolyte lose fluidity, solves the problem that the existing sodium ion battery electrolyte is easy to leak and burn, improves the safety of the electrolyte, and also solves the problem of battery cell volume expansion, meeting the use requirements of sodium ion batteries. The present invention also adds a certain amount of polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material to the electrolyte, and the black phosphorus nanosheet has a serrated edge structure, which has a high selectivity for ion transmission, can effectively capture anions, effectively improve the transmission speed of sodium ions in the electrolyte, and promote the charge and discharge efficiency of the battery. In addition, polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material has good mechanical properties and stability, can effectively reduce the battery cell expansion rate, and improve the cycle life and safety performance of the battery.
[0039] Further, in some embodiments of the present invention, the organic solvent is a mixture of one or more of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, propyl acetate and butyl acetate. Different organic solvents have different ion conductivity and stability, which will affect the conductivity and cycle stability of the battery. The present invention selects one or more of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, propyl acetate or butyl acetate with good ion conductivity and high stability as the organic solvent, thereby improving the performance of the battery. In some embodiments of the present invention, the electrolyte sodium salt is at least one of sodium hexafluorophosphate, sodium perchlorate and sodium tetrafluoroborate. Sodium hexafluorophosphate, sodium perchlorate and sodium tetrafluoroborate have high ionic conductivity and chemical stability, thereby improving the high-efficiency operation of the battery. Moreover, sodium hexafluorophosphate, sodium perchlorate and sodium tetrafluoroborate have high solubility and can be effectively dissolved in organic solvents to ensure the stability and reliability of the battery.
[0040] In some embodiments of the present invention, the concentration of the electrolyte sodium salt in the mixed solution is 0.8-2.0 mol / L; specifically, it can be selected as 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, but not limited thereto. The concentration of the electrolyte sodium salt in the mixed solution directly affects the concentration of the electrolyte sodium salt in the gel electrolyte. Too high or too low a concentration of the electrolyte sodium salt in the gel electrolyte will affect the performance of the gel electrolyte. When the sodium salt concentration is too high, the viscosity of the electrolyte will increase, resulting in obstruction of ion transport and weakening the discharge performance of the battery. On the other hand, too low a sodium salt concentration will result in insufficient ion transport capacity of the electrolyte and reduce the charge and discharge efficiency of the battery. Therefore, it is very important to properly control the concentration of the electrolyte sodium salt for the performance of the gel electrolyte to ensure that the battery has good electrochemical performance and cycle stability.
[0041] In some embodiments of the present invention, the electrolyte sodium salt is dissolved in the organic solvent by stirring for 4-5 hours at a temperature of 20-30° C. The electrolyte sodium salt is fully dissolved in the organic solvent by stirring to facilitate subsequent polymer coating.
[0042] In some embodiments of the present invention, in order to further improve the performance of the gel electrolyte, tris(trimethylsilyl)phosphite and ethyl trifluoroacetate are added to the organic solvent after the electrolyte sodium salt is dissolved. Further, the amount of tris(trimethylsilyl)phosphite added is 1-2% by volume of the organic solvent, and specifically can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0% by volume of the organic solvent, but not limited thereto. The amount of ethyl trifluoroacetate added is 5-10% by volume of the organic solvent, and specifically can be 5%, 5.2%, 5.4%, 5.6%, 5.8%, 1.0% by volume of the organic solvent, but not limited thereto.
[0043] In specific applications, the addition of an appropriate amount of tris(trimethylsilyl)phosphite and ethyl trifluoroacetate in the electrolyte can effectively improve the performance of the battery; this is mainly due to the fact that the above additives can improve the photoelectron conduction performance of the electrolyte, enhance the electrolyte's adsorption capacity for sodium ions, and help improve the electrolyte's ion migration rate and conductivity. In addition, tris(trimethylsilyl)phosphite can also form a dense SEI film, inhibit the dissolution of metal ions, improve the battery's cycle stability and the volume stability of the battery core, and thus improve the battery's safety performance. Moreover, tris(trimethylsilyl)phosphite can reduce the wettability of the solvent in the electrolyte to the electrode, reduce the solvent's wetting rate on the electrode surface, and thus reduce the expansion rate of the battery core. Ethyl trifluoroacetate helps to increase the electrolyte's solubility and conductivity. At the same time, ethyl trifluoroacetate can also provide a stable environment to prevent the degradation of the electrolyte and the degradation of the electrode. However, the addition amount of tris(trimethylsilyl)phosphite and ethyl trifluoroacetate is extremely critical. If the addition amount is too high, the viscosity of the electrolyte will increase, the electrolyte solubility will decrease, and the electrochemical stability will decrease, thus affecting the cycle life and safety of the battery; in addition, if the addition amount is too high, the conductivity of the battery will decrease, affecting the discharge performance of the battery. Conversely, if the addition amount is too low, the cycle life and safety of the battery will be affected, because the insufficient solubility of the electrolyte may cause the electrolyte to crystallize and block the channels in the battery.
[0044] In some embodiments of the present invention, the polymer monomer, the crosslinking agent and the initiator are added to the mixed solution and stirred. The polymer monomer is one or more of methyl methacrylate, ethylene oxide, tetrafluoroethylene and acrylonitrile; the crosslinking agent is one or more of toluene diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and tris(pentafluorophenyl)borane; the initiator is an azo compound, and the azo compound is one or more of azobisisobutyronitrile, azobisisoheptanenitrile and methyl azobisisobutyrate.
[0045] The present invention generates an in-situ thermal cross-linking polymerization reaction under certain conditions by adding a polymer monomer, a cross-linking agent and an initiator, and forms a mesh structure to firmly wrap the liquid electrolyte, thereby solidifying the liquid electrolyte into a gel state, causing the electrolyte to lose fluidity, solving the problem that the existing sodium ion battery electrolyte is easy to leak and burn, improving the safety of the electrolyte, and meeting the use requirements of the sodium ion battery. The present invention selects one or more of methyl methacrylate, ethylene oxide, tetrafluoroethylene, and acrylonitrile as polymer monomers through creative labor. The above polymer monomers can effectively improve the tensile strength, corrosion resistance, high temperature resistance and conductivity of the electrolyte, thereby optimizing the performance of the gel electrolyte. The present invention selects one or more of toluene diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and tris (pentafluorophenyl) borane as cross-linking agents. The above cross-linking agents have good cross-linking effects and adjustable cross-linking properties, and have high heat resistance and chemical resistance, can enhance the stability and durability of the material, are environmentally friendly, and do not contain volatile organic matter. The present invention selects one or more of azobisisobutyronitrile, azobisisoheptanenitrile and methyl azobisisobutyrate as initiators. The initiators have high activity, can initiate chemical reactions at low temperatures, and promote reaction rates.
[0046] In some embodiments of the present invention, the weight proportion of the polymer monomer in the gel electrolyte is 10-30%, the weight proportion of the cross-linking agent is 5-15%, and the weight proportion of the initiator is 1-5%. Specifically, the weight proportion of the polymer monomer in the gel electrolyte can be specifically selected as 10%, 15%, 20%, 25%, 30%, but not limited thereto; the weight proportion of the cross-linking agent can be specifically selected as 5%, 7%, 9%, 11%, 13%, 15%, but not limited thereto; the weight proportion of the initiator can be specifically selected as 1%, 2%, 3%, 4%, 5%, but not limited thereto.
[0047] In practical applications, the dosage of polymer monomers, crosslinking agents and initiators is extremely critical. Too high a dosage of polymer monomers will lead to too high electrolyte viscosity, reduce the ion transmission speed, and thus affect the charge and discharge performance of the battery. However, too low a dosage will lead to unstable gel structure, affect the adhesion and stability of the electrolyte, and easily cause leakage or electrolyte loss. Too high a dosage of initiator will not only increase the cost, but also increase the side reactions, produce gas or solid products, and reduce the purity and stability of the electrolyte; too low a dosage will lead to incomplete polymerization reaction, affecting the structural stability and ion transmission performance of the gel electrolyte. Too high a dosage of crosslinking agent will lead to an overly dense gel structure, limit ion transmission, and affect the power performance of the battery, while too low a dosage will lead to an unstable gel structure, easily cause overflow or loss, and reduce the cycle stability and safety of the electrolyte. The present invention, through creative labor, reasonably selects the dosage of polymer monomers, initiators and crosslinking agents, and the prepared gel electrolyte also has good electrochemical properties and cycle stability. The present invention optimizes the dosage of polymer monomers, cross-linking agents and initiators, so that the polymer monomers produce an in-situ thermal cross-linking polymerization reaction under certain conditions, forming a network structure to firmly wrap the liquid electrolyte, solidify the electrolyte of the sodium ion battery into a gel state, and make the electrolyte lose fluidity. Under the premise of not affecting the electrochemical characteristics of the battery, the problems of easy leakage and combustion of the electrolyte of the existing sodium ion battery and easy expansion of the battery cell are solved, the safety of the electrolyte is improved, and the use requirements of the sodium ion battery are met.
[0048] In some embodiments of the present invention, the mass ratio of polyvinylidene fluoride co-hexafluoropropylene, black phosphorus nanosheets, and graphene nanosheets is 1:(0.001-0.002):(0.001-0.002); specifically, it can be selected as 1:0.001:0.001, 1:0.001:0.0015, 1:0.001:0.002, 1:0.0015:0.001, 1:0.0015:0.0015, 1:0.0015:0.002, 1:0.002:0.001, 1:0.002:0.0015, 1:0.002:0.002, but is not limited to this. The addition amount of the polyvinylidene fluoride-co-hexafluoropropylene coated black phosphorus / graphene material when mixed with the electrolyte is 2-5% of the mass of the electrolyte, specifically 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, but not limited to this.
[0049] In specific applications, the amount of polyvinylidene fluoride co-hexafluoropropylene, black phosphorus nanosheets, and graphene nanosheets will also have a certain impact on the performance of the battery. If the amount of polyvinylidene fluoride co-hexafluoropropylene is too high, the coating layer will be too thick, affecting the ion transmission speed, increasing the impedance between the electrolyte and the electrode, and reducing the battery's charge and discharge efficiency. If the amount is too low, the coating layer will be unstable and unable to effectively protect the black phosphorus or graphene nanosheets, making them susceptible to corrosion by the electrolyte and oxides, shortening the battery's cycle life and affecting the battery's safety. If the amount of black phosphorus nanosheets or graphene nanosheets is too high, it will not only increase the cost, but also cause excessive accumulation of electrode materials, which are prone to agglomeration, affecting the uniformity and stability of the electrode, and limiting the diffusion and insertion / deinsertion rate of sodium ions; while if the amount is too low, it will lead to insufficient electrode active materials, reducing the specific capacity and cycle stability of the sodium ion battery, and affecting the battery's energy density and cycle life. Therefore, the present invention effectively adjusts the dosage of polyvinylidene fluoride-co-hexafluoropropylene, black phosphorus nanosheets and graphene nanosheets to ensure the stability of the coating layer and the uniformity of the electrode material, thereby improving the performance and cycle life of the sodium ion battery.
[0050] In some embodiments of the present invention, the power of the first ultrasonic treatment is 300-500W, and the time is 0.5-1 hour; specifically, the power of the first ultrasonic treatment can be specifically 300W, 350W, 400W, 450W, 500W, but not limited thereto; the time of the first ultrasonic treatment can be specifically 0.6 hour, 0.7 hour, 0.8 hour, 0.9 hour, 1.0 hour, but not limited thereto. The power of the second ultrasonic treatment is 300-500W, and the time is 1-2 hours. Specifically, the power of the second ultrasonic treatment can be specifically 300W, 350W, 400W, 450W, 500W, but not limited thereto; the time of the second ultrasonic treatment can be specifically 1.0 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2.0 hours, but not limited thereto.
[0051] The present invention effectively controls the power conditions of the primary ultrasonic treatment and the secondary ultrasonic treatment so that the components are mixed more evenly, thereby improving the stability of the electrolyte.
[0052] In order to better solve the problems pointed out in the background technology, the present invention also provides a method for preparing a sodium ion battery, injecting the composite gel electrolyte prepared by the above method into the battery, and placing the battery under a temperature condition of 50-80°C for a thermal polymerization cross-linking reaction for 3-8 hours after packaging, so that the composite gel electrolyte forms a gel to prepare a sodium ion battery. Furthermore, the temperature of the thermal polymerization cross-linking reaction can be specifically 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, but not limited thereto. The time of most thermal polymerization cross-linking reactions can be specifically 3h, 4h, 5h, 6h, 7h, 8h, but not limited thereto.
[0053] The present invention adjusts the temperature and time of the thermal polymerization cross-linking reaction so that the polymer monomers are cross-linked to form a network structure that firmly wraps the liquid electrolyte, solidifies the electrolyte of the sodium ion battery into a gel state, and causes the electrolyte to lose fluidity, thereby solving the problems of easy leakage and easy combustion of the existing sodium ion battery electrolyte, improving the safety of the electrolyte, and meeting the use requirements of the sodium ion battery.
[0054] The present application also provides a sodium ion battery, which is prepared according to the above method, and the sodium ion battery includes a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet, and gel is provided between the positive electrode sheet and the separator, and between the negative electrode sheet and the separator; the positive electrode sheet includes a positive electrode collector and a sodium ion positive electrode active material coated on the positive electrode collector, and the positive electrode active material is at least one of sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium iron phosphate and sodium iron sulfate. Based on the above technical scheme, the present invention adopts at least one of sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium iron phosphate and sodium iron sulfate as the sodium ion positive electrode active material, and these materials have good structural stability and electrochemical properties, and can maintain high cycle stability during the charge and discharge cycle.
[0055] The following are some specific embodiments of this specification based on the above technical solution, please refer to Figure 1 , Figure 1 This is an appearance diagram of the electrolyte prepared in Examples 1-2 and Comparative Example 1 of the present application.
[0056] The black phosphorus nanosheets in the following embodiments and comparative examples were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a thickness of 1-10 layers and a sheet diameter of 100nm-5μm. The graphene nanosheets were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a sheet diameter of 1-3μm and a thickness of 1-5nm. Unless otherwise specified, other raw materials are commercially available products.
[0057] Example 1
[0058] A method for preparing a highly safe composite gel electrolyte comprises the following steps:
[0059] S1: dissolving sodium perchlorate in a composite organic solvent consisting of EC:DEC:DMC (the volume ratio of EC:DEC:DMC is 1:1:1) at 25°C to prepare a mixed solution with a concentration of 1.0 mol / L;
[0060] S2: adding acrylonitrile, tri(pentafluorophenyl)borane and azobisisobutyronitrile to the mixed solution, stirring for 2 hours until the mixture is uniformly mixed, to prepare an electrolyte; in the electrolyte, the weight proportion of acrylonitrile is 15%, the weight proportion of tri(pentafluorophenyl)borane is 15%, and the weight proportion of azobisisobutyronitrile is 2%;
[0061] S3: dissolving 1 g of polyvinylidene fluoride-co-hexafluoropropylene in 50 ml of dimethylformamide, and then adding 0.001 g of black phosphorus nanosheets and 0.001 g of graphene nanosheets, performing ultrasound at 300 W for 0.5 h, and then removing the solvent to obtain a polyvinylidene fluoride-co-hexafluoropropylene-coated black phosphorus / graphene material;
[0062] S4: The polyvinylidene fluoride-co-hexafluoropropylene coated black phosphorus / graphene material is mixed with an electrolyte at a mass ratio of 0.03:1, and ultrasonicated at 300 W for 1 hour to obtain a composite gel electrolyte.
[0063] Example 2
[0064] Compared with Example 1, the difference is that in S2, in the electrolyte, the weight proportion of acrylonitrile is 20%, the weight proportion of tri(pentafluorophenyl)borane is 10%, and the weight proportion of azobisisobutyronitrile is 2%. Other conditions are the same as in Example 1.
[0065] Example 3
[0066] Compared with Example 1, the difference is that in S4, the mass ratio of polyvinylidene fluoride-co-hexafluoropropylene-coated black phosphorus / graphene material to electrolyte is 0.05:1, and other conditions are the same as in Example 1.
[0067] Example 4
[0068] Compared with Example 1, the difference is that: in S1, tris(trimethylsilyl) phosphite and ethyl trifluoroacetate are added to the mixed solution with a concentration of 1.0 mol / L, the amount of tris(trimethylsilyl) phosphite added is 1% of the volume of the composite organic solvent, and the amount of ethyl trifluoroacetate added is 6% of the volume of the composite organic solvent. Other conditions are the same as in Example 1.
[0069] Example 5
[0070] Compared with Example 1, the difference is that: in S1, tris(trimethylsilyl) phosphite and ethyl trifluoroacetate are added to the mixed solution with a concentration of 1.0 mol / L, the amount of tris(trimethylsilyl) phosphite added is 2% of the volume of the composite organic solvent, and the amount of ethyl trifluoroacetate added is 8% of the volume of the composite organic solvent. Other conditions are the same as in Example 1.
[0071] Comparative Example 1
[0072] Compared with Example 1, the difference is that the preparation method of the electrolyte in this comparative example only includes step S1.
[0073] Comparative Example 2
[0074] Compared with Example 1, the difference is that: in this comparative example S1, ethyl trifluoroacetate is further added to the mixed solution with a concentration of 1.0 mol / L, and the amount of ethyl trifluoroacetate added is 7% of the volume of the composite organic solvent. Other conditions are the same as those in Example 1.
[0075] Comparative Example 3
[0076] Compared with Example 1, the difference is that: in this comparative example S1, tris(trimethylsilyl) phosphite is further added to the mixed solution with a concentration of 1.0 mol / L, and the amount of tris(trimethylsilyl) phosphite added is 7% of the volume of the composite organic solvent. Other conditions are the same as in Example 1.
[0077] Comparative Example 4
[0078] Compared with Example 1, the difference is that polyvinylidene fluoride-co-hexafluoropropylene is not added in this comparative example S3, and other conditions are the same as those in Example 1.
[0079] Comparative Example 5
[0080] Compared with Example 1, the difference is that no black phosphorus nanosheets are added in this comparative example S3, and other conditions are the same as those in Example 1.
[0081] Comparative Example 6
[0082] Compared with Example 1, the difference is that no graphene nanosheets are added in this comparative example S3, and other conditions are the same as those in Example 1.
[0083] Comparative Example 7
[0084] Compared with Example 1, the difference is that in this comparative example S3, the mass ratio of polyvinylidene fluoride co-hexafluoropropylene, black phosphorus nanosheets, and graphene nanosheets is 2:0.001:0.001, and other conditions are the same as in Example 1.
[0085] Comparative Example 8
[0086] Compared with Example 1, the polyvinylidene fluoride-co-hexafluoropropylene-coated black phosphorus / graphene material is not added to the composite gel electrolyte, and other conditions are the same as those in Example 1.
[0087] Comparative Example 9
[0088] Compared with Example 1, in this comparative example S4, the mass ratio of the polyvinylidene fluoride-co-hexafluoropropylene-coated black phosphorus / graphene material to the electrolyte is 0.1:1, and other conditions are the same as those in Example 1.
[0089] The appearance of the electrolytes prepared in Examples 1-2 and Comparative Example 1 is shown in FIG. Figure 1 As shown, from Figure 1It can be seen that the electrolyte prepared in Comparative Example 1 is transparent in appearance, while the gel electrolytes prepared in Example 1 and Example 2 are opaque and uniform.
[0090] Application Examples
[0091] The sodium iron sulfate positive electrode sheet, the dried diaphragm (glass fiber diaphragm) and the sodium metal sheet are assembled into button batteries in sequence, and the composite gel electrolyte prepared in the embodiment and the comparative example is injected respectively. After packaging, the batteries are baked at 70° C. for 5 hours to cause thermal polymerization and cross-linking reaction to occur, thereby obtaining different sodium ion gel battery products.
[0092] The above different sodium ion gel battery finished products were subjected to performance tests, and the test methods and test results are as follows:
[0093] 1. Test Method
[0094] 1. Normal temperature cycle performance test: At 25°C, the sodium ion battery is charged at a constant current of 1C (nominal capacity) to a voltage of 4.2V, then charged at a constant voltage of 4.2V to a current ≤0.05C, and after 10 minutes of storage, discharged at a constant current of 1C to a cut-off voltage of 2.6V. The above is one cycle of charge and discharge. The sodium ion battery is subjected to 250 charge and discharge cycles at 25°C under the above conditions, and the capacitance retention rate is calculated.
[0095] 2. High temperature cycle performance test: At 55°C, the sodium ion battery is charged at a constant current of 1.0C (nominal capacity) to a voltage of 4.2V, then charged at a constant voltage of 4.2V to a current ≤0.05C, and after 10 minutes of storage, discharged at a constant current of 1C to a cut-off voltage of 2.6V. The above is one charge and discharge cycle. The sodium ion battery is subjected to 250 charge and discharge cycles at 55°C under the above conditions, and the capacitance retention rate is calculated.
[0096] 3. Low-pressure gas production test: At room temperature, the sodium ion battery is charged at a constant current of 0.5C (nominal capacity) to a voltage of 4.2V, then charged at a constant voltage of 4.2V to a current ≤0.05C, then discharged at a constant current of 0.5C to a voltage of 2.6V, and then the initial volume of the battery cell is tested. The battery cells filled with different electrolytes are placed at a constant temperature of 25℃ and 55℃ respectively, and the volume change of the battery cell is tested at the same time point every day. The test is carried out for 7 days, and the volume expansion rate of the battery cell under different conditions is calculated. The test results are shown in Table 1.
[0097] Table 1
[0098]
[0099] As shown in the table above, in the cycle performance test, regardless of whether it is at 25°C or 55°C, the composite gel electrolyte provided by the present invention shows a higher capacity retention rate than the comparative example, indicating that the composite gel electrolyte prepared by the present invention is more stable and can form a more stable and dense SEI film, slowing down the consumption of electrolyte and thus promoting battery life. In the 2.6V low-voltage shelf gas production test, the volume expansion rate of the battery cell using the composite gel electrolyte provided by the present invention is low, which improves the safety performance of the battery.
[0100] In Examples 1-5, polymer coating treatment was used, and the obtained composite gel electrolyte had a high capacity retention rate, and the battery cell containing the composite gel electrolyte obtained in Examples 1-5 had better volume stability. When placed at 25°C and 55°C for 7 days, the volume expansion rate was low, thereby improving the safety performance of the battery.
[0101] It can also be seen from the test results in Table 1 that: compared with Example 1 and Example 2, Example 1 adds more polymer monomers for coating, and the network gel structure formed on the surface of the electrolyte is more stable, and the stability and safety of the obtained electrolyte are higher. Therefore, the capacity retention rate and volume stability of the electrolyte are also better.
[0102] Comparison of Example 1, Examples 4-5 and Comparative Examples 2-3 shows that Examples 4 and 5 add appropriate amounts of tris(trimethylsilyl)phosphite and ethyl trifluoroacetate to the electrolyte, and the two cooperate with each other. The prepared composite gel electrolyte has more excellent electrical properties and volume stability than Example 1 and Comparative Examples 2-3. This is mainly because a certain amount of tris(trimethylsilyl)phosphite can form a dense SEI film, inhibit the dissolution of metal ions, and improve the cycle stability of the battery and the volume stability of the battery core. Moreover, tris(trimethylsilyl)phosphite can reduce the wettability of the solvent in the electrolyte to the electrode, reduce the wetting rate of the solvent on the electrode surface, thereby reducing the expansion rate of the battery core and improving the safety performance of the battery; ethyl trifluoroacetate helps to increase the solubility and conductivity of the electrolyte. Comparative Examples 2 and 3 respectively added only ethyl trifluoroacetate and tris(trimethylsilyl)phosphite. Compared with Example 1, although the electrical properties and volume stability of the composite gel electrolyte were improved to a certain extent, the effect was not as good as adding tris(trimethylsilyl)phosphite and ethyl trifluoroacetate at the same time. Moreover, compared with Examples 4 and 5, the addition amount of tris(trimethylsilyl)phosphite and ethyl trifluoroacetate in Example 5 was larger, and the performance of the composite gel electrolyte obtained was also more excellent.
[0103] By comparing Example 1, Example 3 and Comparative Examples 4-9, it can be seen that in Comparative Example 8, no polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material is added, and the cycle stability of the electrolyte and the volume stability of the battery cell prepared using the same are reduced. This is mainly because the polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material has good mechanical properties and stability, which can effectively reduce the expansion rate of the battery cell and improve the cycle life and safety performance of the battery. However, a large amount of polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material is added to the electrolyte in Comparative Example 9, and the performance of the obtained composite gel electrolyte is reduced instead. This is mainly because the excessive addition of polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material in the electrolyte will increase the interface impedance between the electrode and the electrolyte, resulting in a slower charge transfer rate, reducing the cycle stability of the battery, and causing the battery to perform poorly during long-term cycle charge and discharge. Moreover, excessive addition of polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene materials will increase the internal pressure of the battery cell to a certain extent, affecting the safety and stability of the battery cell. In Comparative Example 4, polyvinylidene fluoride co-hexafluoropropylene coating is not used, and black phosphorus or graphene nanosheets cannot be effectively protected, making them susceptible to corrosion by electrolyte and oxides, shortening the cycle life of the battery. In Comparative Example 5, no black phosphorus nanosheets are added, only graphene nanosheets are added, and the performance of the electrolyte is also reduced. This is mainly because excessive addition of a single type of graphene nanosheets will lead to excessive accumulation of electrode materials, which is prone to agglomeration, affecting the uniformity and stability of the electrolyte, and then affecting the volume stability of the battery cell. In Comparative Example 6, no graphene nanosheets are added, only black phosphorus nanosheets are added, and the performance of the obtained electrolyte is also greatly reduced. On the one hand, due to the addition of a single black phosphorus nanosheet, agglomeration is likely to occur, affecting the uniformity and stability of the electrolyte; on the other hand, black phosphorus nanosheets are easily pulverized in the atmosphere, and the cycle efficiency and cycle stability are poor. The present invention solves the above problems by adding graphene nanosheets on the one hand and polymer coating on the other hand, and the performance of the obtained electrolyte is excellent. Comparative Example 7 uses a large amount of polymer to coat graphene nanosheets and black phosphorus nanosheets, and the performance of the obtained electrolyte is reduced instead. This is mainly because the amount of polyvinylidene fluoride co-hexafluoropropylene is too high, which will lead to an overly thick coating layer, affecting the ion transmission speed, increasing the impedance between the electrolyte and the electrode, and reducing the charge and discharge efficiency of the battery.
[0104] In addition, it should be understood that after reading the contents of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing a highly safe composite gel electrolyte, characterized in that: The following steps are involved: dissolving electrolyte sodium salt in an organic solvent to prepare a mixed solution; Adding polymer monomers, a cross-linking agent and an initiator to the mixed solution to prepare an electrolyte; Dissolving polyvinylidene fluoride co-hexafluoropropylene in dimethylformamide, then adding black phosphorus nanosheets and graphene nanosheets, performing an ultrasonic treatment, and then removing the solvent to obtain a polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material; The polyvinylidene fluoride-co-hexafluoropropylene-coated black phosphorus / graphene material is added to the electrolyte, and a secondary ultrasonic treatment is performed to obtain a composite gel electrolyte.
2. The method for preparing a highly safe composite gel electrolyte according to claim 1, characterized in that: Meet one or more of the following characteristics: (1) The organic solvent is one or a mixture of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, propyl acetate and butyl acetate; (2) The electrolyte sodium salt is at least one of sodium hexafluorophosphate, sodium perchlorate and sodium tetrafluoroborate; (3) The concentration of the electrolyte sodium salt in the mixed solution is 0.8-2.0 mol / L; (4) The electrolyte sodium salt is dissolved in the organic solvent by stirring, the stirring time is 4-5 hours, and the temperature during stirring is 20-30°C.
3. A method for preparing a highly safe composite gel electrolyte according to claim 1 or 2, characterized in that: The following steps are also included: After the electrolyte sodium salt is dissolved, tris(trimethylsilyl)phosphite and ethyl trifluoroacetate are added to the organic solvent.
4. The method for preparing a highly safe composite gel electrolyte according to claim 3, characterized in that: The addition amount of tris(trimethylsilyl)phosphite is 1-2% of the volume of the organic solvent, and the addition amount of ethyl trifluoroacetate is 5-10% of the volume of the organic solvent.
5. The method for preparing a highly safe composite gel electrolyte according to claim 1, characterized in that: Meet one or more of the following characteristics: (1) The polymer monomer is one or more of methyl methacrylate, ethylene oxide, tetrafluoroethylene, and acrylonitrile; (2) The crosslinking agent is one or more of toluene diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and tris(pentafluorophenyl)borane; (3) The initiator is an azo compound, and the azo compound is one or more of azobisisobutyronitrile, azobisisoheptanenitrile and methyl azobisisobutyrate; (4) The polymer monomer, crosslinking agent and initiator are added into the mixed solution and stirred.
6. A method for preparing a highly safe composite gel electrolyte according to claim 1 or 5, characterized in that: The weight proportion of the polymer monomer in the gel electrolyte is 10-30%, the weight proportion of the cross-linking agent is 5-15%, and the weight proportion of the initiator is 1-5%.
7. The method for preparing a highly safe composite gel electrolyte according to claim 1, characterized in that: The mass ratio of the polyvinylidene fluoride co-hexafluoropropylene, black phosphorus nanosheets and graphene nanosheets is 1:(0.001-0.002):(0.001-0.002); the addition amount of the polyvinylidene fluoride co-hexafluoropropylene coated black phosphorus / graphene material when mixed with the electrolyte is 2-5% of the mass of the electrolyte.
8. The method for preparing a highly safe composite gel electrolyte according to claim 1, characterized in that: The power of the first ultrasonic treatment is 300-500W, and the time is 0.5-1 hour; the power of the second ultrasonic treatment is 300-500W, and the time is 1-2 hours.
9. A method for preparing a sodium ion battery, characterized in that: The composite gel electrolyte prepared according to any one of claims 1 to 8 is injected into a battery, and after packaging, the battery is placed under a temperature condition of 50-80° C. for a thermal polymerization cross-linking reaction for 3-8 hours to make the composite gel electrolyte form a gel, thereby preparing a sodium ion battery.
10. A sodium ion battery, characterized in that: Prepared according to the method of claim 9, the sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet, and the gel is provided between the positive electrode sheet and the separator, and between the negative electrode sheet and the separator; the positive electrode sheet comprises a positive electrode collector and a sodium ion positive electrode active material coated on the positive electrode collector, and the positive electrode active material is at least one of sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium iron phosphate and sodium iron sulfate.